Equilibrium: uma abordagem experimental e contextualizada do conceito de equilíbrio dos corpos. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Science education is fundamental to the development of a society, promotes a new world view and offers new possibilities for social welfare. Furthermore, scientific knowledge develops in the students unique skills and abilities that will serve for the rest of their lives. Learning science and its methods is not an easy task, however, it can be very enjoyable, even more so if it is in a playful way. The aim is to apply a didactic sequence with which to change a class to the traditional style, which is one that presents itself with a lot of theory and few opportunities for active student participation in the learning process, to a more active and dialogical style, through experimentation and the contextualization of formal content with everyday situations. In Physics, a good example of this is the teaching of the balance content of the bodies, which is part of the curricular contents proposed by the Parâmetros Curriculares Nacionais. This concept, most of the time, is treated in a decontextualized way and without the opportunity of teaching situations that lead to significant learning, having this work the objective of Planning, executing and evaluating a potentially significant teaching unit with this theme. This situation of teaching not contextualized, was reversed through a teaching situation that offered students the possibility of problematization of the subject to be studied, organization of knowledge and application of the concepts worked, based on a significant learning proposed by David Ausubel.
Keywords: Equilíbrio; Cognitivismo; Lúdico; Aprendizagem significativa; Equilibrium; Cognitivism; Playful; Meaningful learning; CNPQ::CIENCIAS EXATAS E DA TERRA